World War II naval forces : an interactive history adventure - Raum, Elizabeth (North Mankato, Minn. : Capstone Press, 2013)
"Describes the role sailors played during World War II. Readers' choices reveal various historical details"--Provided by publisher.
Joining the Navy -- Sink the Bismark! -- Surprise attack -- Invasion -- A record-breaking war.
Includes bibliographical references and index.
4.3
3-6
Keywords: World War, 1939-1945 -- Naval operations -- Juvenile literature; Sailors -- History -- 20th century -- Juvenile literature; World War, 1939-1945 -- Naval operations; Sailors -- History; World War, 1939-1945 -- Naval operations; Sailors -- History